Probiotics in periodontal therapy - ÖZTÜRK ÖZENER, HAFİZE (AVES PRESS LTD, 2015)
Probiotics, defined as live microorganisms which are beneficial for health, are being used in the treatment of gastrointestinal disorders with success for many years. In recent years, researchers have sparked interest in the efficiency of the probiotics in periodontal health and treatment, based on their effects to support the immune system and suppress pathogenic microorganisms. The role and activity of probiotics in periodontal therapy are evaluated in this review. Probiotic research in periodontology is still in its start up phase. Nevertheless, pioneering results in periodontal health and periodontal therapy are encouraging, and with these data, a certain basis for the generation of further exhaustive and long-term studies are warranted.
Keywords: Microorganism; periodontal diseases; probiotic; therapy